Development of an asteroids game for android implementing agile development techniques - Valencia Sandoval, Carlos Andres (2015)
Ever since the introduction of computer based games, thousands of people have been drawn to play them in a regular basis, and with technology development breakthroughs, more complicated and sophisticated games are being developed, in order supply a demanding and a constantly updating market. The implementation of videogames in mobile devices is not new to the modern society, and it was introduced since the release of the first hand-held devices, however, at the time they were basic games and accessibility to the aforementioned devices was not common. With the popularization of Smartphones, a new and innovative share of the video game market was opened gradually exploited, as a vast amount of users can be targeted to. This project is set to develop a new version of the all-times Atari classic Asteroids, originally launched as an arcade machine game and widely welcomed by the different gamers and video game consumers. In the development of this new adaptation, current and modern game engines, programming paradigms and software development techniques are implemented in order to build a fully-functioning version of the game, playable on mobile devices with the Android operating system. The analysis of the different items set in the scope of the project are discussed and the suitability of the programming resources used throughout the development of the project is concluded, and put in perspective once the final product is obtained and fully playable in different Android devices.